Photocatalytic Water and Wastewater Treatment - Bazargan, Alireza (IWA Publishing, 2022)
This book aims to provide an overview of how photocatalysis can be employed in water and wastewater treatment. Each chapter will attend to a different area of interest, starting with an introduction on the fundamentals of photocatalysis. The covered topics include metal organic frameworks (MOFs), photocatalytic reactor types and configurations, landfill leachate treatment, and life cycle assessment (LCA) of solar photocatalytic wastewater treatment. In addition, the final two chapters provide fresh new insight, by analyzing international patents on photocatalytic materials, solar photocatalysis, and nanotechnology.